Method for treating organic wastewater by using electron-rich spinel anode
By introducing high electron filling metal ions at the tetrahedral sites of the Co3O4 anode material, an electron-rich CoOh3+ center is constructed, which solves the problem of slow ·OH generation kinetics in the electrochemical oxidation system, and realizes efficient degradation of organic wastewater and effective utilization of ·OH.
Patent Information
- Application Number
- CN202411887623.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the existing electrochemical oxidation system, the anode material lacks active media, resulting in slow kinetics of oxidizing H2O into OH, limiting the efficiency of wastewater treatment.
By introducing metal ions M with high electron filling degree, such as Ni, Cu or Zn, at the tetrahedral site of Co3O4, an electron-rich CoOh3+ center is constructed, which weakens the binding strength between the CoOh3+ site and oxygen-containing substances, promotes oxidation of H2O to generate·OH, and inhibits further oxidation of·OH to generate O2.
It realizes efficient generation and rapid desorption of ·OH, improves the degradation efficiency of organic wastewater, and inhibits the peroxidation of ·OH, effectively solving the problem of slow OH generation kinetics in traditional technology.
Smart Images

Figure CN119707038A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sewage treatment, and in particular relates to a method for treating organic wastewater. Background Art
[0002] With the progress of industrialization and urbanization, the treatment of organic wastewater has become an increasingly important issue. A variety of technologies such as advanced oxidation processes, biodegradation, photocatalysis and electrocatalysis are used for wastewater purification. Among them, the electrochemical oxidation (EO) process has the advantages of strong oxidation ability, environmental friendliness, fast reaction kinetics, and modular treatment methods. It is an ideal technology for treating organic pollutants.
[0003] Due to the diversity of active species, there are two reaction mechanisms for pollutant degradation in electrochemical oxidation systems: direct oxidation mediated by slow electron transfer (e - Compared with the indirect oxidation process based on strong oxidizing substances (such as ·OH, redox potential: 2.8V vs.RHE), the indirect oxidation process based on strong oxidizing substances (such as ·OH, redox potential: 2.8V vs.RHE) has greater application prospects in wastewater treatment. The activity of the indirect oxidation system is related to the generation efficiency of ·OH at the anode interface, which involves the oxidative dehydrogenation of H2O molecules (Formula 1). Common anode materials assembled in electrochemical oxidation systems include boron-doped diamond (BDD) and dimensionally stable anodes (DSA, TiO2 / PbO2, TiO2 / Sb2O5-SnO2). In particular, these materials are inactive and have high oxygen evolution reaction (OER) potentials, which effectively inhibit the further oxidation of ·OH to O2 (Formula 2). However, in the preparation process of these anodes, there are problems of high cost and cumbersome procedures. More importantly, due to the lack of active media at the anode, the kinetics of H2O oxidation to ·OH are slow, which restricts the further promotion of this technology in wastewater treatment. Therefore, there is an urgent need to develop highly active anodes to efficiently generate ·OH to eliminate pollutants in wastewater.
[0004] H2O→·OH+H + +e - (1)
[0005] 2·OH→O2+2H + +2e - (2)
[0006] During H2O oxidation, the generation of ·OH is not completely separated from OER. Anode materials with low OER onset potentials also excel in generating ·OH. Spinel oxides (AB2O4) have been widely used in electrochemical oxidation systems due to their excellent electrochemical activity and adjustable electronic structure. Oh 3+ ) than the tetrahedral site (ATd 2+ ) has more low-energy bands and therefore has a higher binding energy with H2O molecules. Td 2+ and B Oh 3+ Strong electron delocalization between sites can effectively induce H2O Oh 3+ The traditional spinel material B Oh 3+ The electron orbital occupancy of the position is low, such as Co Oh 3+ (3d 6 , t 2g 6 e g 0 ), Fe Oh 3+ (3d 5 , t 2g 3 e g 2 ), Mn Oh 3+ (3d 4 , t 2g 4 e g 0 ), when combined with H2O molecules, B Oh 3+ The hybridization between 3d and O 2p orbitals is too strong, so that the generated adsorbed ·OH cannot be separated from the anode interface, resulting in the peroxidation of ·OH to O2. Therefore, it is necessary to modify the traditional spinel oxide to weaken the B Oh 3+ The binding strength between the sites and oxygen-containing species is enhanced, and the adsorbed ·OH is released during water oxidation, thereby achieving ·OH-mediated wastewater purification in the electrocatalytic oxidation system. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for treating organic wastewater using electron-rich spinel anode, which can effectively promote the rate-limiting step of H2O oxidation to generate ·OH and strictly inhibit ·OH from further oxidation to generate O2 and lose its oxidizing ability.
[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0009] A method for treating organic wastewater using an electron-rich spinel anode comprises the following steps: using the electron-rich spinel anode to electrolyze the organic wastewater, wherein the electron-rich spinel anode is used to introduce a metal ion M with a high electron filling degree into the tetrahedral site of Co3O4 so that it can effectively couple with M Td 2+ The electron repulsion between O atoms and Co Oh 3+ The π contribution between the O atoms and the electron-rich Co Oh 3+ Center, weaken Co Oh 3+ The binding strength between the site and the oxygen-containing species induces the oxidative dehydrogenation of H2O molecules to generate ·OH, and inhibits the further oxidation of ·OH to generate O2, thereby achieving efficient degradation of organic wastewater mediated by ·OH;
[0010] The metal ion M is Ni, Cu or Zn.
[0011] In the above method for treating organic wastewater using an electron-rich spinel anode, preferably, the molar ratio of the metal ion M to Co is (0.05-0.2):1.
[0012] In the above method for treating organic wastewater using electron-rich spinel anode, preferably, the metal ion M is Cu, and the molar ratio of Cu to Co is (0.08-0.1): 1. More preferably, the molar ratio of Cu to Co is 0.1:1.
[0013] In the present invention, our research shows that the amount of metal ions M with high electron filling degree has a key influence on the performance of the anode. Too much or too little amount of metal ions M will affect the effect of its action and the mechanism of action when the anode works. Taking copper as an example, if the amount of copper is too little, the repulsion between copper and oxygen atoms is weak, which is not conducive to the construction of electron-rich Co Oh 3+ center, which is not conducive to weakening Co Oh 3+ The bonding strength between the site and the oxygen-containing substance, *OH is easily peroxidized to generate oxygen. Excessive use of copper will lead to Co Oh 3+ There are too many electrons around, which weakens Co Oh 3+The binding energy with H2O inhibits the generation of ·OH. That is, if the amount of metal ion M is too much or too little, the water oxidation path will be changed, the generation of ·OH will be inhibited, and the water oxidation path will be changed from *H2O→*OH→·OH of the present invention to *H2O→*OH→*O→O2. After water oxidation generates *OH, desorption cannot occur, and it will be overoxidized to generate O2. At this time, the oxygen evolution performance of the material is better. Reasonable control of the amount of metal ion M is conducive to the generation of ·OH, and after water oxidation generates *OH, it will quickly desorb into free ·OH and will not continue to oxidize to O2. At this time, the oxygen evolution performance of the material is extremely poor. That is, in the present invention, it is necessary to accurately control the molar ratio of metal ion M to Co. In a more preferred scheme, the metal ion M is Cu, and the molar ratio of Cu to Co is (0.08-0.1):1. Further preferably, the molar ratio of Cu to Co is 0.1:1.
[0014] In the above-mentioned method for treating organic wastewater using an electron-rich spinel anode, preferably, the preparation method of the electron-rich spinel anode includes the following steps: evenly mixing ethylene glycol, a copper source, a cobalt source and deionized water, then adding urea, hexadecyltrimethylammonium bromide and ammonium fluoride, and continuing to stir evenly until a transparent solution is obtained; immersing the FTO base in the above-mentioned transparent solution, and then placing it in a reactor with the conductive surface facing up, and conducting a hydrothermal reaction; after the reaction is completed, naturally cooling, washing with water, drying, and calcining to obtain the electron-rich spinel anode.
[0015] The preparation method of the present invention is conducive to the preparation of electron-rich Co Oh 3+ The electron-rich spinel anode in the center, the above process path and raw material types are conducive to the preparation of the specific electron-rich spinel anode of the present invention.
[0016] In the above method for treating organic wastewater using an electron-rich spinel anode, preferably, the FTO base is first ultrasonically cleaned in an acetone solution and an ethanol solution, then ultrasonically cleaned with deionized water, and then dried.
[0017] In the above method for treating organic wastewater using electron-rich spinel anode, preferably, the volume of ethylene glycol, copper source, cobalt source and deionized water is 8-10:2:5:30, wherein the molar concentration ratio of copper source to cobalt source is (0.5-2):4, the mass ratio of urea, hexadecyltrimethylammonium bromide and ammonium fluoride is 0.5:0.5:(1.4-1.5), and the ratio of urea to ethylene glycol is 8-10mL:0.5g. More preferably, the volume of ethylene glycol, copper source, cobalt source and deionized water is 10:2:5:30, wherein the molar concentration ratio of copper source to cobalt source is (0.5-2):4, the mass ratio of urea, hexadecyltrimethylammonium bromide and ammonium fluoride is 0.5:0.5:1.455, and the ratio of urea to ethylene glycol is 10mL:0.5g.
[0018] In the above method for treating organic wastewater using electron-rich spinel anode, preferably, the reaction temperature is controlled to be 110-130°C and the time is 10-14h during the hydrothermal reaction. More preferably, the reaction temperature is controlled to be 120°C and the time is 12h during the hydrothermal reaction.
[0019] In the above method for treating organic wastewater using electron-rich spinel anode, preferably, calcination is performed in two stages, first calcining at 340-360°C for 1.5-2.5h, then calcining at 540-560°C for 1.5-2.5h. More preferably, calcining is performed at 350°C for 2h, then calcining at 550°C for 2h.
[0020] In the present invention, the above process parameters, including the type and ratio of raw materials, including the hydrothermal reaction parameters and the control of calcination conditions, are conducive to the construction of electron-rich Co in the electron-rich spinel anode. Oh 3+ Center, which is conducive to preparing the electron-rich spinel anode required by the present invention.
[0021] In the above method of treating organic wastewater using electron-rich spinel anode, preferably, when using electron-rich spinel anode to electrolyze organic wastewater, the electron-rich spinel anode is used as the working electrode, the counter electrode is a Pt sheet, the reference electrode is Ag / AgCl, and the electrolysis voltage is 1.5-2.5V vsAg / AgCl. An electrochemical workstation (CHI 760E, Shanghai Chenhua, China) is used to provide a constant voltage. Before the reaction starts, the two electrodes are inserted into the solution, and the immersion area of the working electrode is 3.75-4.25cm 2 The reaction time is 2-2.5 hours. Stir the whole reaction process, draw the solution with a syringe, filter with a 0.45 μm polytetrafluoroethylene (PTFE) membrane, and collect the reaction solution.
[0022] In the above method for treating organic wastewater using electron-rich spinel anode, preferably, the electrolytic reaction device is a 100-150mL single-chamber electroreactor, and the pollutant concentration in the organic wastewater is 10-20mgL -1 .
[0023] The present invention modifies the traditional spinel oxide by 2+ The introduction of metals into the tetrahedral sites of Co3O4 constructs electron-rich Co Oh 3+ Center, improves B Oh 3+ The electron orbital occupancy of the Cu 2+ For example, specifically, due to Cu 2+ The electron orbital is 3d 9 (e 4 t2 5 ), so in spinel oxide, Cu 2+ The interaction between the O atoms is electron repulsive, while the Co 3+ There is a π contribution between the Cu and O atoms. 2+ It can effectively couple electron repulsion and π contribution, Cu 2+ The electrons of Co are more inclined to the octahedral 3+ , which is conducive to the formation of Co Oh 3+ rich electron centers, thereby increasing B Oh 3+ The electron orbital occupancy of Co 3+ The binding energy with oxygen-containing substances is reduced, which promotes the rapid desorption of adsorbed *OH into free ·OH, effectively oxidizes pollutants, and has a high utilization rate of ·OH.
[0024] In the present invention, Ni 2+ / Cu 2+ / Zn 2+ Introducing the tetrahedral sites of Co3O4 to construct electron-rich Co Oh 3+ Center, weaken Co Oh 3+ The binding strength between the site and the oxygen-containing species releases OH for pollutant oxidation. 2+ / Cu 2+ / Zn 2+ The electron orbitals are 3d 8 (e 4 t2 3 ), 3d 9 (e 4 t2 5 ), 3d 10 (e 4t2 5 ), so M in spinel oxide 2+ The interaction between Co and O atoms is electron repulsion, while 3+ There is a contribution to π between Cu and O atoms. 2+ It can effectively couple the electron repulsion and π-donation effect, which is beneficial to the formation of Co Oh 3+ Electron-rich center. Through systematic experiments and electrochemical characterization, the generation efficiency of OH and the pollutant removal performance in the electrochemical oxidation system were explored. The results show that the electron-rich spinel anode of the present invention has excellent effect. The present invention provides a theoretical basis for in-depth understanding of the formation of active substances in the electrochemical oxidation system and provides guidance for the design and synthesis of wastewater purification electrodes with excellent and stable performance.
[0025] The spinel oxide anode synthesized by the present invention can efficiently remove a variety of organic pollutants, and has a lower barrier to generate ·OH. The electron-rich spinel anode system constructed by the present invention achieves efficient generation of ·OH, while inhibiting its overoxidation to generate O2, providing a theoretical and technical basis for treating organic wastewater.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] In the method for treating organic wastewater using an electron-rich spinel anode of the present invention, a specific electron-rich spinel anode is used to effectively promote the rate-limiting step of oxidizing H2O to generate ·OH, and efficiently treat the organic wastewater. In addition, the reasonable selection of the reaction conditions of the system can effectively achieve efficient degradation of pollutants in organic wastewater while strictly inhibiting the further oxidation of ·OH to generate O2 and lose oxidation ability, effectively solving the problem of slow kinetics of oxidizing H2O to ·OH in traditional electro-oxidation systems, and opening up a new stable and efficient wastewater treatment method. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 For different Cu 2+ Cu doping concentration x Co 3-x Performance diagram of O4 anode degradation of Rhodamine B.
[0030] Figure 2 Cu under different applied constant voltagex Co 3-x Performance diagram of O4 anode degradation of Rhodamine B.
[0031] Figure 3 The transition metal concentration is 0.1 mol L -1 Performance diagram of Rhodamine B degradation by Co3O4 doped with different transition metals.
[0032] Figure 4 For different Cu 2+ Cu doping concentration x Co 3-x Schematic diagram of the electrochemically active surface area of the O4 anode.
[0033] Figure 5 For different Cu 2+ Cu doping concentration x Co 3-x Schematic diagram of the cumulative concentration of ·OH in the O4 anode system.
[0034] Figure 6 Cu x Co 3-x Figure 3. Cyclic experimental diagram of degradation of Rhodamine B by O4 anode system.
[0035] Figure 7 Cu x Co 3-x Experimental diagram of active species quenching during the removal of Rhodamine B in the O4 anode system.
[0036] Figure 8 For different Cu 2+ Cu doping concentration x Co 3-x EPR spectrum of O4 anode system.
[0037] Fig. 9 Cu x Co 3-x Degradation performance diagram of different pollutants in O4 anode system. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0039] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0041] The specific determination method of the content of each product in the present invention is as follows:
[0042] The concentration change of rhodamine B was measured at a wavelength of 554 nm using an ultraviolet-visible spectrophotometer. The model of the ultraviolet-visible spectrophotometer used was U-3900, Hitachi Ltd, Japan.
[0043] The concentration of hydroxylation products was determined by high performance liquid chromatography (HPLC, LC-20A, Shimadzu, Japan).
[0044] Embodiment 1:
[0045] Cu x Co 3-x O4 as an example, Rhodamine B was selected as the treatment object, which is a typical pollutant in printing and dyeing wastewater.
[0046] In this example, the treatment object is rhodamine B, which is common in typical printing and dyeing wastewater. First, 10-20 mg L -1 Measure 50 mL of Rhodamine B into a beaker. Add 50 mM sodium sulfate to the beaker. Stir and dissolve the solution into a 100-150 mL reactor. x Co 3-x O4 is the working electrode, Pt sheet is the counter electrode, Ag / AgCl is the reference electrode, constant voltage is applied and stirred to start the reaction. During the reaction, samples are taken with a syringe at specified intervals and immediately filtered with a 0.45 μm polytetrafluoroethylene (PTFE) membrane.
[0047] The specific preparation method of the anode material in this embodiment is as follows:
[0048] First, a piece of FTO (1.5 cm × 4 cm) was ultrasonically cleaned in acetone solution and ethanol solution for 15 min, then ultrasonically cleaned twice with deionized water and dried at 60 °C. -1 5mL of 0.4mol L copper nitrate solution -1Cobalt nitrate solution and 30mL deionized water are mixed into a uniform solution. Then, 0.500g urea, 0.050g hexadecyltrimethylammonium bromide and 1.455g ammonium fluoride are added, and stirring is continued until a uniform and transparent solution is obtained. Then, the pretreated FTO is immersed in the 100mL reactor lining containing the above solution, with the conductive side facing up, and stored at 120°C for 12h. After natural cooling, remove the electrode and wash it with deionized water. After drying, the electrode is placed in a muffle furnace, calcined at 350°C and 550°C for 2h respectively, cooled to room temperature, and finally Cu x Co 3-x O4 electrode material (wherein the molar ratio of copper to cobalt is 0.1:1).
[0049] The amount of copper nitrate solution was changed to 0.05 mol L -1 and 0.15 mol L -1 , respectively prepared Cu x Co 3-x O4-1 (molar ratio of copper to cobalt is 0.05:1) and Cu x Co 3-x O4-3 (the molar ratio of copper to cobalt is 0.15:1).
[0050] Embodiment 2:
[0051] Zn x Co 3-x O4 as an example, Rhodamine B was selected as the treatment object, which is a typical pollutant in printing and dyeing wastewater.
[0052] In this example, the treatment object is rhodamine B, which is common in typical alkaline printing and dyeing wastewater. First, 10-20 mg L -1 Measure 50 mL of Rhodamine B into a beaker. Add 50 mM sodium sulfate to the beaker. Stir and dissolve the solution into a 100-150 mL reactor. x Co 3-x O4 is the working electrode, Pt sheet is the counter electrode, Ag / AgCl is the reference electrode, and the reaction is started while applying a constant voltage and stirring. During the reaction, samples are taken with a syringe at specified intervals and immediately filtered with a 0.45μm polytetrafluoroethylene (PTFE) membrane.
[0053] The specific preparation method of the anode material in this embodiment is as follows:
[0054] First, a piece of FTO (1.5 cm × 4 cm) was ultrasonically cleaned in acetone solution and ethanol solution for 15 min, then ultrasonically cleaned twice with deionized water and dried at 60 °C. -15mL of 0.4mol L zinc nitrate solution -1 Cobalt nitrate solution and 30mL deionized water are mixed into a uniform solution. Then, 0.500g urea, 0.050g hexadecyltrimethylammonium bromide and 1.455g ammonium fluoride are added, and stirring is continued until a uniform and transparent solution is obtained. Then, the clean FTO is immersed in a 100mL reactor liner containing the above solution with the conductive side facing up, sealed and transferred to a drying oven, and stored at 120°C for 12h. After natural cooling, the electrode is removed and washed with deionized water. After drying, the electrode is placed in a muffle furnace, calcined at 350°C and 550°C for 2h respectively, cooled to room temperature, and finally Zn x Co 3-x O4 electrode material (wherein the molar ratio of zinc to cobalt is 0.1:1).
[0055] Embodiment 3:
[0056] Take Ni x Co 3-x O4 as an example, Rhodamine B was selected as the treatment object, which is a typical pollutant in printing and dyeing wastewater.
[0057] In this example, the treatment object is rhodamine B, which is common in typical alkaline printing and dyeing wastewater. First, 10-20 mg L -1 Measure 50 mL of Rhodamine B into a beaker. Add 50 mM sodium sulfate to the beaker. Stir and dissolve the solution into a 100-150 mL reactor. x Co 3-x O4 is the working electrode, Pt sheet is the counter electrode, Ag / AgCl is the reference electrode, and the reaction is started while applying a constant voltage and stirring. During the reaction, samples are taken with a syringe at specified intervals and immediately filtered with a 0.45μm polytetrafluoroethylene (PTFE) membrane.
[0058] The specific preparation method of the anode material in this embodiment is as follows:
[0059] First, a piece of FTO (1.5 cm × 4 cm) was ultrasonically cleaned in acetone solution and ethanol solution for 15 min, then ultrasonically cleaned twice with deionized water and dried at 60 °C. -1 5mL of 0.4mol L nickel nitrate solution -1Cobalt nitrate solution and 30mL deionized water are mixed into a uniform solution. Then, 0.500g urea, 0.050g hexadecyltrimethylammonium bromide and 1.455g ammonium fluoride are added, and stirring is continued until a uniform and transparent solution is obtained. Then, the clean FTO is immersed in a 100mL reactor liner containing the above solution, with the conductive side facing up, and transferred to a drying oven after sealing, and stored at 120°C for 12h. After natural cooling, remove the electrode and wash it with deionized water. After drying, the electrode is placed in a muffle furnace, calcined at 350°C and 550°C for 2h respectively, cooled to room temperature, and finally Ni x Co 3-x O4 electrode material (wherein the molar ratio of nickel to cobalt is 0.1:1).
[0060] The degradation effect of the present invention on rhodamine B and its mechanism of action are discussed in detail below through the specific experimental results of Examples 1-3.
[0061] like Figure 1 As shown in the figure, the degradation performance of Rhodamine B in different catalytic systems is compared. Under constant voltage conditions, Cu x Co 3-x The O4 system can remove almost 100% of rhodamine B within 2 h, which is much better than Co3O4 and CuCo2O4 (reaction conditions: starting voltage of 2 V, sodium sulfate concentration of 50 mM, rhodamine B concentration of 10 mg L -1 ), the preparation process of CuCo2O4 is the same as that of Example 1, except that the amount of copper source is increased. x Co 3-x The copper source dosage of O4-1 is 0.05 mol L -1 , Cu x Co 3-x The copper source dosage of O4-3 is 0.15 mol L -1 ), the results showed that different copper source dosages had a great influence on the degradation performance of rhodamine B. When the copper source dosage was 0.1 mol L -1 The degradation performance is optimal.
[0062] like Figure 2 As shown in the figure, by setting different voltage conditions, it is found that when the applied voltage is 2V, Cu x Co 3-x The O4 system has the best performance in degrading Rhodamine B. Figure 3-Figure 5 As shown, when the applied voltage is 2 V and the concentration of the introduced transition metal is 0.1 mol L -1 When only Cu x Co 3-x The O4 system can remove almost 100% of Rhodamine B within 2 h, indicating that Cu 2+The introduction of is more conducive to the construction of electron-rich Co Oh 3+ Co3O4 at the site. Combining the electrochemically active surface area and the cumulative concentration of OH, it can be seen that Cu x Co 3-x The electrochemically active surface area of O4 can reach 11.56 mF cm -2 , and the cumulative concentration of OH is the largest, due to Cu 2+ The electron orbital is 3d 9 (e 4 t2 5 ), so in Co3O4, Cu 2+ The interaction between the O atoms is electron repulsive, while the Co 3+ There is a π contribution between the Cu and O atoms. 2+ It can effectively couple electron repulsion and π contribution, which is conducive to the formation of Co Oh 3+ Rich electron centers, weakening Co Oh 3+ The binding strength between the site and the oxygen-containing species releases OH. In addition, the Cu x Co 3-x Cyclic experiment of degradation of Rhodamine B by O4 system, such as Figure 6 As shown, the average removal rate of 7 cycle experiments is about 94%, indicating that the system has high electrochemical stability.
[0063] Figure 7 and Figure 8 Shows Cu x Co 3-x Active species in O4 system. The active species quenching experiment was carried out using tert-butyl alcohol (TBA) as hydroxyl radical quencher and methanol (MeOH) as hydroxyl radical and sulfate radical quencher. x Co 3-x A quencher was added to the O4 system for performance testing, and it was preliminarily determined that ·OH was the main active species in the degradation process of organic pollutants. Figure 8 In the EPR test, a small amount of liquid was taken out during the reaction, and 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) scavenger was added to test the signal peak of DMPO-·OH. The results showed that there was a strong DMPO-·OH signal during the reaction, which further indicated that ·OH was the main active species in the degradation process of organic pollutants. The strong oxidizing ability of this active species can quickly attack organic pollutants in a short time to degrade them.
[0064] like Fig. 9 As shown, Cu was tested x Co 3-xThe degradation performance of the O4 system on different pollutants showed that the system had excellent degradation performance on both electron-withdrawing pollutants (NB: nitrobenzene) and electron-donating pollutants (PE: phenol, CBZ: carbamazepine, TC: tetracycline, SMX: sulfamethoxazole, 4-CP: p-chlorophenol) (reaction conditions: starting voltage of 2 V, sodium sulfate concentration of 50 mM, pollutant concentration of 10 mg L -1 ), demonstrating that this system has broad application potential in actual water pollution treatment.
[0065] It can be seen from the above embodiments that the present invention constructs an electron-rich B Oh 3+ The electrochemical oxidation system of spinel oxidation of H2O achieves rapid degradation of organic pollutants in wastewater. In this system, due to the excellent electrochemical activity and adjustable electronic structure of spinel oxide, A Td 2+ and B Oh 3+ Strong electron delocalization between sites can effectively induce H2O Oh 3+ site is oxidized to ·OH. In addition, Cu 2+ The electron repulsion between O atoms and Co 3+ The π-donating effect between the O atoms and the Co Oh 3+ Rich electron centers, weakening Co Oh 3+ The binding strength between the site and the oxygen-containing species, the released OH makes Cu x Co 3-x O4 has excellent electrochemical oxidation performance, and it will have great application prospects in the field of actual organic wastewater treatment.
Claims
1. A method for treating organic wastewater using electron-rich spinel anodes, characterized in that: The following steps are involved: Electrolyze organic wastewater using an electron-rich spinel anode, wherein the electron-rich spinel anode is used to introduce a metal ion M with a high electron filling degree into the tetrahedral site of Co3O4, so that it can effectively couple M Td 2+ The electron repulsion between O atoms and Co Oh 3+ The π contribution between the O atoms and the electron-rich Co Oh 3+ Center, weaken Co Oh 3+ The binding strength between the site and the oxygen-containing species induces the oxidative dehydrogenation of H2O molecules to generate ·OH, and inhibits the further oxidation of ·OH to generate O2, thereby achieving efficient degradation of organic wastewater mediated by ·OH; The metal ion M is Ni, Cu or Zn.
2. The method for treating organic wastewater using electron-rich spinel anode according to claim 1, characterized in that: The molar ratio of the metal ion M to Co is (0.05-0.2):
1.
3. The method for treating organic wastewater using electron-rich spinel anode according to claim 2, characterized in that: The metal ion M is Cu, and the molar ratio of Cu to Co is (0.08-0.1):
1.
4. The method for treating organic wastewater using electron-rich spinel anode according to any one of claims 1 to 3, characterized in that: The preparation method of the electron-rich spinel anode comprises the following steps: uniformly mixing ethylene glycol, a copper source, a cobalt source and deionized water, then adding urea, hexadecyltrimethylammonium bromide and ammonium fluoride, and continuing to stir uniformly until a transparent solution is obtained; immersing the FTO base in the transparent solution, and then placing it in a reactor with the conductive surface facing upward to perform a hydrothermal reaction; after the reaction is completed, naturally cooling, washing with water, drying, and calcining to obtain the electron-rich spinel anode.
5. The method for treating organic wastewater using electron-rich spinel anode according to claim 4, characterized in that: The FTO base is firstly ultrasonically cleaned in an acetone solution and an ethanol solution, then ultrasonically cleaned with deionized water, and then dried.
6. The method for treating organic wastewater using electron-rich spinel anode according to claim 4, characterized in that: The volume of ethylene glycol, copper source, cobalt source and deionized water is 8-10:2:5:30, wherein, The molar concentration ratio of the copper source to the cobalt source is (0.5-2):4, the mass ratio of urea, hexadecyltrimethylammonium bromide and ammonium fluoride is 0.5:0.5:(1.4-1.5), and the ratio of urea to ethylene glycol is 8-10mL:0.5g.
7. The method for treating organic wastewater using electron-rich spinel anode according to claim 4, characterized in that: During the hydrothermal reaction, the reaction temperature is controlled at 110-130°C and the reaction time is 10-14h.
8. The method for treating organic wastewater using electron-rich spinel anode according to claim 4, characterized in that: The calcination is carried out in two stages, first at 340-360°C for 1.5-2.5h, and then at 540-560°C for 1.5-2.5h.
9. The method for treating organic wastewater using electron-rich spinel anode according to any one of claims 1 to 3, characterized in that: When the electron-rich spinel anode is used to electrolyze organic wastewater, the electron-rich spinel anode is used as the working electrode, the counter electrode is a Pt sheet, the reference electrode is Ag / AgCl, and the electrolysis voltage is 1.5-2.5V vsAg / AgCl.
10. The method for treating organic wastewater using electron-rich spinel anode according to any one of claims 1 to 3, characterized in that: The electrolytic reaction device is a 100-150mL single-chamber electroreactor, and the pollutant concentration in the organic wastewater is 10-20mgL -1 .
Citation Information
Patent Citations
Anode material of high-temperature solid oxide electrolysis cell and composite anode material
CN104934613A
Process for preparation of metal oxides nanocrvstals and their use for water oxidation
US20200056295A1